Penerapan metode cutting plane terhadap optimisasi jumlah produksi - Mohamad Fausi; Himmawati Puji Lestari (Jurnal Kajian dan Terapan Matematika, 2022)
This study aims to optimize the amount of bakpia production in Bakpia Madania SMEs in order to obtain maximum profits. The optimization problem for Bakpia Madania UKM is that the number of products produced must be an integer (in packaging) or not in the form of a fraction. The research method used to solve these problems is the cutting plane method. The cutting plane method is a method used to solve linear integer programming, both pure and mixed integers with the addition of a new constraint called gomory. Gomory constraint is given if the value of the decision variable is not unanimous (fractional value). The results showed that the optimum solution using the plane cutting method at UKM Bakpia Madania resulted in the production of original packaged bakpia as many as 364 boxes, original packaged bakpia as many as 175 boxes, chocolate bakpia as many as 21 boxes, and cheese bakpia as much as 40 boxes and the maximum profit obtained was Rp. 2,221,820 with the difference / increase in profit with the company's initial profit of Rp. 47,460.